Koperasi Syariah - Lia Olivia Zahara; Ayu Andini; Tia Syifana; Intan Nadzifa; Laily Nurul Hidayah; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The aim of this research is to describe the meaning of sharia cooperatives, both in terms of the history of the founding of sharia cooperatives, the function and objectives of sharia cooperatives, the activities of legal business entities or laws or regulations regarding sharia cooperatives, and the profile of one of the relevant institutions. This research method uses a library approach, namely a research approach method that comes from books and journals that are appropriate to the topic of discussion and research focus. The results of the literature review in this research conclude that sharia cooperatives are run guided by sharia laws, thereby ensuring benefits in their activities. Sharia cooperatives must be run by people who understand sharia economics and can convey their knowledge to the community as cooperative members, so that people understand the advantages of transacting in sharia cooperatives, and choose sharia cooperatives rather than transacting in economic institutions with a capitalist system to carry out economic activities. Cooperatives can provide an effort to overcome poverty in society. Sharia cooperatives have products and mechanisms that are based on the Koran and Hadith.